Naringin as a non-antibiotic agent for multi-species oral biofilm control: in vitro antimicrobial mechanisms and in vivo safety in a rat caries model - Song, Jie; Liu, Mingqi; Yasen, Yizinigaer; Zhao, Ying; Wu, Zeyu; Zhao, Jin (Frontiers in Microbiology, 2025)
IntroductionDental caries is driven by dysbiosis of oral biofilms. Conventional antibiotics easily disrupt oral commensal balance, creating an urgent need for natural, non-antibiotic agents that can target cariogenic biofilms without causing ecological collapse.MethodsThe antimicrobial and antibiofilm efficacy of Naringin was evaluated in vitro against planktonic and biofilm states of Streptococcus mutans, Streptococcus sobrinus, Streptococcus sanguinis (mono-species), and their multi-species consortium. Minimum inhibitory/bactericidal concentrations (MIC/MBC) and minimum biofilm inhibitory/reduction concentrations (MBIC/MBRC) were determined. Effects on acid production, extracellular polysaccharide (EPS) synthesis, and bacterial adhesion to hydroxyapatite (HAP) were mechanistically investigated. In vivo, a rat caries model induced by the multi-species consortium was topically treated with Naringin (2 × MIC, MIC, 1/2 × MIC) for 4 weeks. Caries lesions were evaluated using Keyes scoring and micro-computed tomography. Oral microbiota, serum biochemistry, and histopathology were analyzed for safety assessment.ResultsNaringin exhibited potent, concentration-dependent antimicrobial activity. MICs were 1.00 mg/mL for S. mutans and S. sanguinis, 0.50 mg/mL for S. sobrinus, and 0.50 mg/mL for the multi-species consortium. Naringin at MBIC (2 mg/mL for multi-species) significantly disrupted biofilm architecture, reduced viable bacteria, and inhibited EPS synthesis. It maintained biofilm pH above 5.5 (the critical threshold for enamel demineralization), inhibited lactate production, and reduced multi-species bacterial adhesion to HAP by 68.3% at MIC. In vivo, Naringin (MIC) significantly reduced Keyes scores on smooth and sulcal surfaces by over 60%, preserved enamel integrity, and rebalanced the oral microbiota without inducing mucosal irritation or systemic toxicity.DiscussionNaringin, a natural non-antibiotic agent, effectively inhibits the “adhesion-biofilm-acid-EPS” cascade of multi-species cariogenic biofilms. Its selective efficacy against pathogens and favorable in vivo safety profile position it as a promising ecological agent for caries prevention by addressing oral dysbiosis at its root.